Li2FeSiO4 nanorods bonded with graphene for high performance batteries1. Issue 18 (14th May 2015) - Yang, Jinlong; Hu, Lin; Zheng, Jiaxin; He, Daping; Tian, Leilei; Mu, Shichun; Pan, Feng
<x xml:space="preserve">Abstract</x> We synthesized a novel 2D hybrid material composed of Li2FeSiO4 nanorods (LFSNRs) anchored on graphene.